Fundamentals of English grammar - Azar, Betty Schrampfer, 1941- (Pearson Education, 2003)
A classic developmental skills text for lower-intermediate and intermediate students of English as a second or foreign language, Fundamentals of English Grammar is a reference grammar as well as a stimulating and teachable classroom text. While keeping the same basic approach and material as in earlier editions, the third edition more fully develops communicative and interactive language-learning activities. Some of the new features are: numerous "real communication" opportunities; more options for interactive work in Paris and groups; additional open-ended communicative tasks for both speaking and writing; expanded error-analysis exercises; interesting and lively new exercise material; and new appendices for phrasal verbs and prepositions. - Back cover.